Narrativas Que Se Construyen A Partir Del Significado de la Experiencia de Tatuarse el Cuerpo en un Grupo de Adultos Jóvenes Pertenecientes a Familias Monoparentales (2018)
The present of this research is to analyze the narratives of the experience of tattooing the body of 4 young adults belonging to single-parent families, with the participation of 2 women and 2 men, based on this, an analysis of 3 categories was established. response to the objectives proposed at the beginning of the investigation. The information was collected from an unstructured interview that allowed to identify in the narrations the motivations and significant experiences of expressing in an indelible way in the body its history.